2018
DOI: 10.1002/cphc.201701241
|View full text |Cite
|
Sign up to set email alerts
|

Method Evaluations for Adsorption Free Energy Calculations at the Solid/Water Interface through Metadynamics, Umbrella Sampling, and Jarzynski's Equality

Abstract: Considerable interest in characterizing protein/peptide-surface interactions has prompted extensive computational studies on calculations of adsorption free energy. However, in many cases, each individual study has focused on the application of free energy calculations to a specific system; therefore, it is difficult to combine the results into a general picture for choosing an appropriate strategy for the system of interest. Herein, three well-established computational algorithms are systemically compared and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Details could be found in our previous studies. 23 Entropic and Enthalpic Components of the Adsorption Free Energy. In this study, our efforts have been exerted into estimating the entropic and enthalpic components of the adsorption free energy to thoughtfully unravel the thermodynamic characteristics of peptide adsorption at the surface− water interface.…”
Section: ■ Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Details could be found in our previous studies. 23 Entropic and Enthalpic Components of the Adsorption Free Energy. In this study, our efforts have been exerted into estimating the entropic and enthalpic components of the adsorption free energy to thoughtfully unravel the thermodynamic characteristics of peptide adsorption at the surface− water interface.…”
Section: ■ Methodologymentioning
confidence: 99%
“…12,22 Previously, we have systemically evaluated the benefits and pitfalls of each method and proposed a general principle of how to prescreen the sampling methods according to the interfacial characteristics of the system. 23 The free energy decomposition has illustrated that the binding of peptide/protein with a surface is considered as the delicate balance between the interactions of the adsorbate with both the surface and solvent. 24 It has been further revealed that the water phase provides a repelling force against peptide adsorptions, whereas the surface−peptide interaction serves as the driving force to peptide adsorption.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts were done to critically compare the performance of different free-energy calculation methods [139,[222][223][224][225][226][227][228]. This is a non-trivial task, which becomes even more difficult if kinetic properties are the target.…”
Section: Theoretical and Computational Approaches To Kineticsmentioning
confidence: 99%
“…This can be theoretically formulated using the principle of maximum entropy (pMaxEnt) [236]. Pitera and Chodera [237] showed how to implement pMaxEnt by a linear bias applied on a single simulation with an unknown force constant (the Lagrangian multiplier) that can be obtained iteratively or on-the-fly during the simulation [228,[237][238][239]. Alternatively, instead of searching for the Lagrangian multiplier, one can perform multiple simulations in parallel and couple them with an harmonic potential centred on the value of the equilibrium observable of interest, the so called replica-averaging approach [240][241][242].…”
Section: Theoretical and Computational Approaches To Kineticsmentioning
confidence: 99%